Membangun Budaya Kelas Konstruktif Melalui Prinsip Servant leadership di Universitas Islam Negeri Maulana Malik Ibrahim Malang - Ramadhan, Narendra Jumadil Haikal; Abidin, Munirul; Rizki, Ahmad Abu; Abrarrah, Khairunisyah; Arfan, Ode Rahman (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research explores the implementation of servant leadership as a strategy to overcome the problem of unconstructive classroom culture in the university environment. In the context of Islamic education, the importance of creating a learning culture that is balanced between intellectual, spiritual, and moral aspects is the main foundation. Support from the literature on constructivism and previous research shows that a constructive classroom culture has a positive impact on academic achievement, critical thinking skills, and the development of ethical values in Islamic education. Servant leadership, as a proposed solution, emphasizes service as the main approach, with leaders focusing on listening and responding to the needs of their class members. This research will explain in depth how the application of servant leadership by the Class Leader can form constructive classroom conditions at Maulana Malik Ibrahim State Islamic University Malang. Through qualitative methods with observation and in-depth interviews. The findings are expected to contribute to a more comprehensive understanding of the relationship between servant leadership and constructive classroom culture, with the potential to provide a basis for policy development or decisions related to leadership principles in creating positive and inclusive classroom conditions